- Design of control system based on Arduino to Air Blast Freezer with heating cabin: - - Erham, Eddy (ReTII, 2020)
The rapid development of technology has prompted researchers to continue creating new products or adding new facilities to existing products. For example, adding new facilities to the refrigeration system is being carried out. This research will develop a heating cabin facility in the Air Blast Freezer. For this reason, a special condenser as a heating source will be added and control design will be carried out both for the Freezer and for a special condenser. For control design, this Arduino will be uploaded with the control system program so that it can function as a controller. The results obtained are the refrigeration system can maintain both the temperature of the coolant cabin and the heating cabin at T setpoint -12 0C with Tcut-off = -14 0C and Tcut-in = -10 0C and at T setpoint 44 0C with Tcut-off = 46 0C and Tcut-in = 420C , respectively. In addition, the electric power consumption in the heating cabin is 275.44 Watt and the comparison cabin is 288.36 Watt. The difference in power is 12.92 Watts or 4.48%.